2020
DOI: 10.1007/s12011-020-02377-4
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Serum Electrolytes and Trace Elements Role in the Pathophysiology of COVID-19

Abstract: All the world is involved in the COVID-19 disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Coronavirus is a positive-sense RNA and has an envelope. There is no specific drug for this disease and treatment methods are limited. Malnutrition and electrolyte imbalance can make dysfunction in the immune system and impairment of the immune system causes increasing the risk of infection. Understanding the aspects of biological features of the virus will help the development of diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
2
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 68 publications
2
57
2
3
Order By: Relevance
“…It inhibits virus replication in the host cells. The virulence property of SARS-CoV is mainly depends on its penetration property into pneumocytes [ 48 ]. Sodium selenite stops the viral infectivity by preventing the entry of coronaviruses into healthy host cells [ 49 ].…”
Section: Trace Elements In Immune Response Against Covid-19 and Othermentioning
confidence: 99%
See 2 more Smart Citations
“…It inhibits virus replication in the host cells. The virulence property of SARS-CoV is mainly depends on its penetration property into pneumocytes [ 48 ]. Sodium selenite stops the viral infectivity by preventing the entry of coronaviruses into healthy host cells [ 49 ].…”
Section: Trace Elements In Immune Response Against Covid-19 and Othermentioning
confidence: 99%
“…Decreased serum Se concentration causes accumulation of mutations in the genome of HIV, influenza A and SARS coronavirus, indicating the changes in the virulence is associated genetic structures [ 52 ]. Several studies demonstrated in animal model showed selenium deficiency increases mutation of viral genome which leads to increased pathogenicity and mortality [ 48 , 53 ].
Fig.
…”
Section: Trace Elements In Immune Response Against Covid-19 and Othermentioning
confidence: 99%
See 1 more Smart Citation
“…255,256 Selenium is a crucial component of the enzyme system of our body and a to a great extent, deficiency of selenium leads to improper functioning of the cellular immunity and increases the probability of oxidative stress which can further amplify the risk of viral genome mutation, enhanced pathogenicity and difficulty in treating the infection hence growing mortality. 254,257,258 Although evidence is limited yet early experience in COVID-19 patients shows that adequate selenium levels were associated with a better recovery rate than COVID-19 patients from the cities or high selenium levels had a high cure rate and low mortality as compared to low selenium levels areas. 259 The effectiveness of selenium in viral infections is supported by previous poliovirus infection, HIV, and epidemic hemorrhagic fever.…”
Section: Role Of Micronutrients Vitamins and Other Trace Elements Imentioning
confidence: 99%
“…255,272,274,275 By this means, micronutrient insufficiencies have been identified as an international public health concern. 258,276,277 A recent study by Darnton-Hill reported that selenium, iron, potassium, sodium, calcium, magnesium, folic acid, copper, and zinc play an important role in improving the immune physiology and patient recovers earlier and decrease hospital stay among COVID-19 patients. 258 In support of that, several studies across the world advocated the importance of a balanced diet with relevant nutrients and trace elements as an extenuation approach to build robust immune physiology to fight back the COVID-19 pandemic.…”
Section: Role Of Micronutrients Vitamins and Other Trace Elements Imentioning
confidence: 99%